Scientific analysis of pharmaceutical logistics in Ukraine - L. M. Unhurian; O. I. Bielyaieva; N. A. Prylypko; I. V. Vyshnytska (Kazimierz Wielki University, 2016)
Theoretical positions and methodological aspects of pharmaceutical logistics are conceptually generalized. Directions and features of becoming of national pharmaceutical logistics (depth of search - 1956-2005) are determined. The logistic providing of search stages and advancement of drugs is developed. The logistic mechanisms of management of commodity stocks of wholesale pharmaceutical enterprises and pharmacies, and also principles of modeling of logistic flows of pharmaceutical firms are improved. An integral index that characterizes the level of logistic service it is offered. The principles of conception of the logistic management of wastes of pharmaceutical branch are offered. The generalized index of width of development of pharmacy networks is developed.